Bio-realistic and versatile artificial dendrites made of anti-ambipolar transistors - Yifei Yang; Mingkun Xu; Tianhang Zhang; Chenfei Miao; Juan Lyu; Jing Pei; Peng Li; Guoqi Li; Si Wu; Huanglong Li (Neuromorphic Computing and Engineering)
The understanding of neural networks as neuron-synapse binaries has been the foundation of neuroscience, and therefore, the emerging neuromorphic computing technology that takes inspiration from the brain. This dogma, however, has been increasingly challenged by recent neuroscience research in which the downplayed dendrites were found to be active, dynamically unique and computationally powerful. To date, research on artificial dendrites is scarce and the few existing devices are still far from versatile or (and) bio-realistic. A breakthrough is hampered by the limited available physical mechanisms in mainstream device architectures. Here, we experimentally demonstrate a bio-realistic and versatile artificial dendrite made of WSe _2 /MoS _2 heterojunction-channel anti-ambipolar (AAB) transistor, which can closely mimic the experimentally recorded non-monotonic dendritic Ca ^2+ action potential that underpins various sophisticated computations. Spiking neural network simulations reveal that the incorporation of this nonconventional but bio-realistic dendritic activation enhances the robustness and representational capability of the network in non-stationary environments. By further exploiting the memristive effect, dendritic AAB transistor can naturally mimic Ca ^2+ -mediated regulation of synaptic plasticity (meta-plasticity) at dendritic spine, an important homeostatic phenomenon due to dendritic modulation. The invention of dendritic AAB transistor enriches the family of neuromorphic transistors and represents a major advance in diversifying the functionality of transistors.